Development of an extremely robust automotive suspension system using intelligent active force control - Mailah, Musa (Faculty of Mechanical Engineering, 2006)
This report describes both theoretical and experimental studies of a quarter-car vehicle suspension system that incorporates a number of control schemes in which a number of responses or charac teristics were rigorously inve stigated. Particular focus is on the application of a very practical robust control scheme known as active force control (AFC) that is expected to render any forms of disturbances on the system to be effectively compensated. These disturbances are mostly in the form of various modelled road profiles (terrains) that the unsprung mass (tyre or wheel) comes in direct contact with and which in turn are transmitted to the sprung mass (body) of the system causing undesirable vibration or shaking that may cause discomfort to the ‘passenger’.